2005
DOI: 10.1002/crat.200410347
|View full text |Cite
|
Sign up to set email alerts
|

Studies on spontaneous formation of 1D nanocrystals of silicon carbide

Abstract: Novel nanostructures have been formed spontaneously during the thermolysis of mixtures containing halogenohydrocarbons and Si-related compounds as a reducing agent in a calorimetric bomb. Elemental analysis, XRD (X-Ray Diffraction), EELS (Electron Energy Loss Spectroscopy), EDX (Energy Disspersive X-ray spectroscopy), IR (InfraRed spectroscopy), Raman spectroscopy, HR SEM (High Resolution Scanning Electron Spectroscopy) and TEM (Transmission Electron Spectroscopy) were used to determine the chemical compositio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…The 3C cubic zincblende structure (also known as the b-SiC) has been confirmed as a dominant polytype for SiC nanowires and also for the ones obtained in combustion synthesis [15]. The nanofibres' axis lies usually in the [1 1 1] direction but the objects with [1 0 0] orientation have been also observed [7].…”
Section: Introductionmentioning
confidence: 94%
“…The 3C cubic zincblende structure (also known as the b-SiC) has been confirmed as a dominant polytype for SiC nanowires and also for the ones obtained in combustion synthesis [15]. The nanofibres' axis lies usually in the [1 1 1] direction but the objects with [1 0 0] orientation have been also observed [7].…”
Section: Introductionmentioning
confidence: 94%
“…4(b). Because electron diffraction streaks are always perpendicular to growth direction, [19][20][21][22][23][24][25][26] it may be evident from the SAED that stacking planes are {111} and growth direction of nanorods in the dendrite arm is [111]. All the nanorods in the bundles or bunches, are seen to be aligned in the same direction.…”
Section: Resultsmentioning
confidence: 99%
“…Contrary to this, the nanocrystalline SiC samples have a Raman band at 900 cm -1 . This feature could be affected by finite size effect in nanocrystalline samples and may also suggest the presence of multiple politypes of SiC [7].…”
Section: Methodsmentioning
confidence: 96%
“…While the total duration (including a heat-up of reaction promoter) was ca 1.5 s, the main combustion period lasted 0.36 s only. Following the procedure outlined earlier [7], the emission spectrum was recorded during the reaction and the nearly blackbody radiation revealed that the average temperature during the combustion was within 1800 ± 100 K. As a matter of fact, the high-temperature direct synthesis of SiC from the elements is postulated [9,10] to occur in the same temperature range. The de-fluorination of PTFE using Si elemental is strongly dependent on the initial pressure and combustion atmosphere [8].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation